2000
DOI: 10.1093/carcin/21.5.079
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor upregulates E1AF that induces oral squamous cell carcinoma cell invasion by activating matrix metalloproteinase genes

Abstract: Hepatocyte growth factor (HGF) is thought to play a role in cell motility and invasion. Matrix metalloproteinases (MMPs) have been implicated in invasion and metastasis of tumor cells. We have previously reported that the Ets-oncogene family transcription factor E1AF positively regulates transcription of MMP genes in transient expression assays and that overexpression of the E1AF gene confers an invasive phenotype on breast cancer cells. Here we examined the effect of HGF on E1AF and MMP gene expression in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 28 publications
2
56
1
Order By: Relevance
“…(5)(6)(7) Indeed, it has been reported that HGF ⁄ SF promotes cell migration and angiogenesis in human esophageal SCC, (27) upregulates the expression of proangiogenic cytokines interleukin (IL)-8 and vascular endothelial growth factor (VEGF) through the activation of mitogen-activated protein ⁄ extracellular signal-regulated kinase kinase (MEK) and phosphatidylinositol 3¢-kinase (PI3K) signaling pathways in HNSCC, (28) and induces the invasion of oral SCC by matrix metalloproteinase genes through the upregulation of the transcription factor E1AF. (29) However, how HGF ⁄ SF and MET signaling cascade affects the expression of each specific downstream functional gene has not yet been elucidated in detail. In addition, there is a growing number of reports that describe the translational regulation of growth factors or their receptors, including HGF and MET, in cancer by miR-NA, (30,31) but less reports describe the regulation of miRNA expression by a growth factor itself to date.…”
Section: Discussionmentioning
confidence: 99%
“…(5)(6)(7) Indeed, it has been reported that HGF ⁄ SF promotes cell migration and angiogenesis in human esophageal SCC, (27) upregulates the expression of proangiogenic cytokines interleukin (IL)-8 and vascular endothelial growth factor (VEGF) through the activation of mitogen-activated protein ⁄ extracellular signal-regulated kinase kinase (MEK) and phosphatidylinositol 3¢-kinase (PI3K) signaling pathways in HNSCC, (28) and induces the invasion of oral SCC by matrix metalloproteinase genes through the upregulation of the transcription factor E1AF. (29) However, how HGF ⁄ SF and MET signaling cascade affects the expression of each specific downstream functional gene has not yet been elucidated in detail. In addition, there is a growing number of reports that describe the translational regulation of growth factors or their receptors, including HGF and MET, in cancer by miR-NA, (30,31) but less reports describe the regulation of miRNA expression by a growth factor itself to date.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several investigators reported that HGF up-regulated matrix-degrading enzymes. [31][32][33][34] We also reported that the augmentation of HGF/c-met signal upregulated proMMP9, proMMP1, and uPA in a renal cell carcinoma cell line, Caki-1. 18 In this oral SCC cell system, we also examined the effect of HGF on the activity of the gelatinase produced by BHY and HN cells.…”
Section: Discussionmentioning
confidence: 99%
“…Taq DNA polymerase (Takara Biomedicals, Kusatsu, Japan) was added to the mixture at a final concentration of 0.05 U/ l, and the reaction was carried out in a Takara Thermal Cycler MP (Takara Biomedicals) under the following conditions: 94°C for 3 min and then 94°C for 1 min, 55°C for 1.5 min, 72°C for 2.5 min for 30 cycles, and extension at 72°C for 4 min. To determine whether conditions were adequate for semi-quantitative RT-PCR, we reverse-transcribed 0.05, 0.5, 5, and 10 g of total RNA and amplified the fragments under the same PCR conditions with different numbers of cycles (18,22,26,30,34 cycles). We used 5 g of cytoplasmic or total RNA as a template for reverse transcription and 30 cycles of PCR amplification for c-met and 22 cycles for GAPDH.…”
Section: Rt-pcrmentioning
confidence: 99%
“…Antisense oligonucleotides to Ets-1 reduced invasion in oral cancers. In the same system, HGF induced invasion was partially dependent upon PEA3/E1AF mediated induction of MMP9 (Hanzawa et al, 2000). Dominant-negative constructs consisting of the Ets domain of Ets-2 inhibit anchorage independent growth and invasion of BT20 breast carcinoma cells (Sapi et al, 1998) and PPC-1 prostate carcinoma cells (Foos and Hauser, 2000).…”
Section: Etsmentioning
confidence: 93%